Ugrofinizmy w języku staropruskim: Finno-Ugric Borrowings in Old Prussian - Witczak, Krzysztof Tomasz (Przegląd Wschodnioeuropejski, 2021)
The paper discusses 9 Old Prussian words suspected of being borrowed from a Finno-Ugric source. The following words are verified as Finno-Ugricisms: OPrus. jūrī ‘sea’ (← FV. *järwä ‘lake, sea’); OPrus. kadegis ‘juniper’ (← BF. *kataŋa ‘id.’ ← Ur. *kača ‘resin’); OPrus. kaywe ‘mare’ (← BF. *keewe ‘female horse or reindeer’ < Ur. *kewe ‘female animal’); OPrus. kērdan ‘time’ (← FV. *kerta ‘succession, order, time’); OPrus. *palwe in toponymy (← FU. *palγɜ ‘village’); OPrus. *salavō ‘island’ (← FU. *sala-wɜ ‘island; dry place in the swamp’ < Ur. *sala); OPrus. sylecke ‘Baltic herring’ (← BF. *silakka ‘id.’ ← Ur. śilä ‘fat’); OPrus. wargien ‘copper’ (← FU. *würγɜnɜ ‘id.’).